FLUVIAL TERRACES AS INDICATORS OF QUATERNARY GEOMORPHOLOGICAL DYNAMICS: A CASE STUDY IN THE PAULISTA PERIPHERAL DEPRESSION - Lupinacci, Cenira Maria [UNESP]; Souza, Tissiana de Almeida de (Uniao Geomorfologia Brasileira, 2019)
Fluvial terraces are considered key relief markers to understand environmental changes in the nature time scale, acting as paleo-indicators of morphogenetic processes occurred during the Quaternary, especially the Holocene. The absolute dating method through Luminescence has been considered very effective for obtaining the ages of the material constituting fluvial terraces, once it can be applied to several materials, in different environmental conditions and through different techniques. Therefore, the aim of this study is to provide information on the evolution of the relief during the Quaternary, analyzing the sector of the Peripheral Depression, countryside of Sao Paulo state. For this, the geochronological evolution of the fluvial terraces of Passa Cinco River Upper Basin, located in the municipalities of Ipeuna and Itirapina, was interpreted through the analysis of Optically Stimulated Luminescence (OSL) data, granulometry of the material composing the deposits, and comparison with academic studies which performed dating methods in the fluvial terraces of Parana Sedimentary Basin. The ages of 6 fluvial terrace samples were obtained, these results allowed the proposal of a geochronological sequence of 4 phases for Passa Cinco River Upper Basin: 1) between 37,700 and 32,250 years B.P.; 2) between 3,000 and 2,000 years B.P.; 3) 1,470 years B.P; and 4) 600 years B.P. Considering the proposal of other authors for the region, it was evaluated that part of these phases were developed in drier climates than the current, demonstrating the quaternary dynamics of evolution of the basin.
Keywords: Quaternary; Fluvial terraces; Paulista Peripheral Depression